Technological characterization of pregelatinized flour based on corn and cassava bran for the formulation of infant cereal flour - Frez, Fabio Luiz Vieira; Sarache, Gabriel; Vieira, Luan Felipe Quirino; Raniero, Ghiovani Zanzotti; Monteiro, Antonio Roberto Giriboni (Seven Editora, 2023)
Dietary fibers are an important component for intestinal health, including for children, so with the aim of developing and technologically evaluating a cereal flour for children, corn and cassava bran were chosen as raw materials because they are accessible products and very widespread in the population’s daily diet. The flours were prepared as follows: T1 with 80% (w/w) corn and 20% (w/w) cassava and T2 with 60% (w/w) corn and 40% (w/w) cassava, plus 5% (w/w) distilled water in both. In order to have instant characteristics, the flours were pregelatinized through extrusion and had their expansion index, water absorption index (WAI) and water solubility index (WSI) measured. In addition, the moisture content, bulk and tapped densities were measured and used to analyze the flowability of the products. The expansion index and densities decreased as the amount of cassava bran increased, a behavior that was expected due to the addition of fibers. The WAI and WSI did not differ significantly between the samples, contrary to the findings of other authors. The flowability analysis shows that the flours developed do not flow easily. In general, cassava bran has an impact on the characteristics of pregelatinized flour, which can cause problems in its production, and further studies are needed to understand nutritional and acceptability issues. DOI:https://doi.org/10.56238/interdiinovationscrese-022